2019
DOI: 10.1186/s13028-019-0497-6
|View full text |Cite
|
Sign up to set email alerts
|

Iron treatment of pregnant sows in a Danish herd without iron deficiency anemia did not improve sow and piglet hematology or stillbirth rate

Abstract: BackgroundAnemia characterized by low hemoglobin concentration (HbC) is common in indoor housed pregnant sows. Iron is essential for hemoglobin synthesis and a number of metabolic processes including DNA synthesis and regulation of enzyme systems. In sows, anemia has been linked to lower HbC in piglets and increased occurrence of stillbirths. Therefore, the main objective of this study was to evaluate the effect of iron injection on hematology of pregnant sows and their offspring. Other objectives were to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
1
10
0
3
Order By: Relevance
“…The incidence of stillbirth at sow level in this study (47.9%) is higher in comparison with those in Brazil (27.8% to 33.1%) (Lucia et al, 2002;Borges et al, 2005), it is, however, similar to that in Belgium (48%) (Vanderhaeghe et al, 2010) and in Denmark (44%) (Rangstrup-Christensen et al, 2017). The stillbirth rate in this study (5.2%), is within the range of reported results (4.1%-7.5%) (Lucia et al, 2002;Borges et al, 2005;Vanderhaeghe et al, 2010;Rangstrup-Christensen et al, 2017;Bhattarai et al, 2019a;2019b). Unfavorable association between farrowing duration and stillbirth has been previously substantiated (Van Dijk et al, 2005;Canario et al, 2006;Baxter et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of stillbirth at sow level in this study (47.9%) is higher in comparison with those in Brazil (27.8% to 33.1%) (Lucia et al, 2002;Borges et al, 2005), it is, however, similar to that in Belgium (48%) (Vanderhaeghe et al, 2010) and in Denmark (44%) (Rangstrup-Christensen et al, 2017). The stillbirth rate in this study (5.2%), is within the range of reported results (4.1%-7.5%) (Lucia et al, 2002;Borges et al, 2005;Vanderhaeghe et al, 2010;Rangstrup-Christensen et al, 2017;Bhattarai et al, 2019a;2019b). Unfavorable association between farrowing duration and stillbirth has been previously substantiated (Van Dijk et al, 2005;Canario et al, 2006;Baxter et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…Hypoxia is a condition where the oxygen flow is compromised leading to a decrease in hepcidin synthesis and consequently a higher flow of iron to the circulation. Additionally, literature showed that sow hemoglobin levels have decreased ( Bhattarai, 2019 ) and litter size increased ( Hansen, 2019 ) during the last years and consequently the sow might not be capable of covering the iron needs of the piglets. However, even though litter size had a significant effect on Hb levels in this trial, no linear relationship could be detected between litter size and baseline Hb level.…”
Section: Discussionmentioning
confidence: 99%
“…However, this treatment is highly challenging considering its possible adverse effects on sow's iron metabolism, the risk of iron toxicity and insufficiency of the molecular machinery involved in transplacental iron transport. Indeed, supplementation of sows at various stages of pregnancy, using various iron supplements (iron salts/chelates, iron dextran) administered orally or parenterally has no significant impact on the improvement of iron status of newly born piglets and has not been proven in prophylaxis of neonatal IDA in piglets [16,[19][20][21][67][68][69][70][71][72]. Despite these negative results, in this study we attempted to test the efficacy of prenatal oral supplementation with SFP through administration of this compound to pregnant sows.…”
Section: Discussionmentioning
confidence: 99%
“…However, while in preterm human neonates the shortage of stored iron results from shortened period of iron deposition in the fetal liver, in term newborn piglets the main reason is the physiological inability of pregnant sow to meet iron demand for the greater number of fetuses. Several studies have attempted to increase the level of iron hepatic iron stores in fetuses by treating pregnant sows with iron supplements [16][17][18][19][20][21][22]. However, supplementation of sows at various stages of pregnancy, using various iron supplements administered orally or parenterally has no significant impact on the improvement of the iron status of newborn piglets and thus does not prevent suckling animals from becoming anemic (reviewed in Reference [23]).…”
Section: Introductionmentioning
confidence: 99%